2020
DOI: 10.9734/jgeesi/2020/v24i130189
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Faecal Sludge from Pit Latrines to Guide Management Solutions in Cape Coast, Ghana

Abstract: This study characterised faecal sludge from public ventilated improved pit (VIP) latrines in Cape Coast to assess their potential impact on the environment and to guide the selection of appropriate management solutions. The paper also estimates the amount of beneficial resources wasted due to the lack of a faecal sludge (FS) treatment facility. The study employed a quantitative design involving laboratory analysis of FS sampled from 13 purposively sampled VIP latrines in Cape Coast, Ghana. Sampling activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Besides, the lack of consistent sampling methods could have a significant impact on the results (Niwagaba et al 2014;Strande 2014a). These results are supported by previous studies found elsewhere (Gudda et al 2017), Cameroon (Maffo et al 2019), and Ghana (Awere et al 2020). A similar trend was detected in FS parameters affecting the dewaterability of FS among and within the OSS containments.…”
Section: Variation Of Fs Characterization Among Four Containmentssupporting
confidence: 92%
See 1 more Smart Citation
“…Besides, the lack of consistent sampling methods could have a significant impact on the results (Niwagaba et al 2014;Strande 2014a). These results are supported by previous studies found elsewhere (Gudda et al 2017), Cameroon (Maffo et al 2019), and Ghana (Awere et al 2020). A similar trend was detected in FS parameters affecting the dewaterability of FS among and within the OSS containments.…”
Section: Variation Of Fs Characterization Among Four Containmentssupporting
confidence: 92%
“…Knowing FS physical-chemical characteristics while still in containment can contribute towards a better understanding of the future design criteria and appropriate selection of FS treatment technologies. Despite numerous studies on FS characteristics (Niwagaba et al 2014;Ahmed et al 2019;Awere et al 2020), the variability of physical-chemical characteristics of FS affected by the type of OSS containments and season has not been documented based on type. Moreover, the physical-chemical predictor of FS also varies with season.…”
Section: Introductionmentioning
confidence: 99%
“…However, stratification occurs with continual inputs of “fresh” excreta to containments, and storage is not analogous to anaerobic digestion that is process controlled at treatment facilities to optimize microbial degradation, . Changes to wastewater during passive anaerobic storage have been observed to level off after 1 week, , and average biochemical oxygen demand (BOD 5 ) concentrations of almost 10 000 mg/L have been observed in the bottom regions of pit latrines …”
Section: Why Does Terminology Matter?mentioning
confidence: 99%
“…39 Changes to wastewater during passive anaerobic storage have been observed to level off after 1 week, 40,41 and average biochemical oxygen demand (BOD 5 ) concentrations of almost 10 000 mg/L have been observed in the bottom regions of pit latrines. 42 Wastewater in containment is also different from what is termed "sludges" in sewer to treatment systems. Fractions of wastewater in this case are not termed "sludge" until they have undergone additional processes.…”
Section: Wastewater Streams From Human Feces Are Not All the Same And...mentioning
confidence: 99%
“…There is a considerable amount of research investigating characteristics of sewage sludge-derived biochar but less on faecal sludge biochar ( Gold et al , 2018 ). Many studies exist on the properties of faecal sludge itself ( Awere et al , 2020 ; Bassan et al , 2013 ; Fanyin-Martin et al , 2017 ; Lama et al , 2022 ; Schoebitz et al , 2014 ; Septien et al , 2020 ). Only a handful of articles examine properties of faecal sludge biochar and these studies have a diverse range of objectives including biochar as a soil amendment to increase lettuce yields ( Woldetsadik et al , 2018 ), biochars solid fuel characteristics ( Krueger et al , 2020 ), cadmium adsorption by biochar ( Koetlisi & Muchaonyerwa, 2017 ), recovery of ammonium in urine by biochar ( Bai et al , 2018 ) and energy balance analysis of slow pyrolysis of human manure ( Liu et al , 2014 ).…”
Section: Introductionmentioning
confidence: 99%